FAO commodity review and outlook 1979-1980. - Food and Agriculture Organisation of the United Nations (Rome: Food and Agriculture Organisation of the United Nations, 1979)
This volume highlights and analyses world market developments affecting agricultural, fishery and forestry products. Commodities covered include sugar, beverages and tropical crops; cereals, cassava and livestock products; oilseeds, fats and oils; agricultural raw materials (cotton, jute, hides and skins; fishery products; forestry products among others.
lje 14/06/2017
Loans
Keywords: Agricultural industries; Produce trade; Primary commodities; Commercial products